Psychometri properties of the Cognitive Emotion Regulation Questionnaire in a sample of Iranian population - Besharat, mohammad ali; Bazzazian, saeeideh (Advances in Nursing & Midwifery, 2015)
Abstract Background and Aims: Emotion regulation refers to the ability to understand emotions and modulate emotional experience and expressions. Emotions are managed and regulated according to processes and techniques that may be employed automatically or purposely, as well as consciously or unconsciously. The main purpose of this study was to examine psychometric properties of the Cognitive Emotion Regulation Questionnaire. Methods and methods: Four hundred and seventy eight Iranian volunteers (226 males, 252 females) were included in this study. All participants were asked to complete the 18-item version of the Cognitive Emotion Regulation Questionnaire (CERQ), Depression Anxiety Stress Scale (DASS), and the Mental Health Inventory (MHI-28). Findings: Test-retest reliability and internal consistency of the CERQ were examined at satisfactory levels. The CERQ scales of self-blame, rumination, catastrophizing, and other-blame revealed significant positive associations with depression, anxiety, stress and psychological distress, as well as significant negative associations with psychological well-being. The remaining scales of CERQ including acceptance, positive refocusing, planning, positive reappraisal, and putting into perspective revealed significant negative associations with depression, anxiety, stress and psychological distress, as well as significant positive associations with psychological well-being. Conclusion: It was concluded that the 18-item version of the CERQ can be considered as a reliable and valid scale to measure cognitive coping strategies in Iranian samples. Keywords: Cognitive Emotion Regulation Questionnaire, Reliability, Validity, Psychometry REFERENCES American Psychiatric Association (2000). Diagnostic and Statistical manual for mental disorders (5th ed). Washington: APA. Besharat MA (2005). [Psychometric properties of Depression Anxiety Stress Scale (DASS-21) in clinical and general population]. Research Report. University of Tehran. (Persian). Besharat MA (2006). [Reliability and validity of the Mental Health Inventory-34]. Daveshvar Raftar. 7(3) 1-8. (Persian). Besharat MA (2009) [Reliability and validity of the Mental Health Inventory-28]. Forensic Medicine. 54(2) 87-91. (Persian). Besharat MA (2010) [Perfectionism and anger]. Journal of Psychology. 17(1) 27-46. (Persian) 1393 راهب ،84 هرامش ،24 هرود / 68 ناراکمه و تراشب یلعدمحم رتکد Besharat MA Mohammad Mehr R (2009) [Psychometric evaluation of Anger Rumination Scale]. Nursing & Midwifery Quarterly. 19(3) 36-43. Bronson MB (2000). Recognizing and supporting the development of self-regulation in young children. Young Children. 55(2) 32-37. Calkins SD Howse RB (2004). Individual differences in self-regulation: Implications for childhood adjustment. In P. Philippot & R. S. Feldman (Eds.). The regulation of emotion (pp. 307-332). Mahwah, NJ: Lawrence Erlbaum Associates, Publishers. Carver CS et al (1989). Assessing coping strategies: a theoretically based approach. Journal of Personality and Social Psychology.56(2) 267-283. Cronbach LJ (1970). Essentials of psychological testing. New York: Harper and Row International. Eckman P (1993). Facial expression and emotion. American Psychologist. 48(4) 384-392. Eisenberg N et al (2000). Dispositional emotionality and regulation: Their role in predicting quality of social functioning. Journal of Personality and Social Psychology 78(1) 136-157. Endler NS Parker JDA (1994). Assessment of multidimentional coping: Task, emotion and avoidance strategies. Psychological Assessment. 6(1) 50-60. Feldman-Barrett L et al (2001). Knowing what you’re feeling and knowing what to do about it: Mapping the relation between emotion differentiation and emotion regulation. Cognition and Emotion. 15(6) 713-724. Flavell JH et al (2002). Cognitive Development. Upper Saddle River, NJ: Prentice Hall. Folkman S Lazarus RS (1988). Manual of the Ways of Coping Questionnaire. Palo Alto: Consulting Psychologists Press. Folkman S Moskowitz JT (2004). Coping: Pitfalls and promise. Annual Review of Psychology. 55(6) 745-774. Garnefski N et al (2005). Psychological distress and cognitive emotion regulation strategies among farmers who fell victim to the foot-and-mouth crisis. Personality and Individual Differences. 38(6) 1317-1327. Garnefski N et al (2002). The relationship between cognitive emotion regulation strategies and emotional problems. European Journal of Personality. 16(5) 403-420. Garnefski N Kraaij V (2006). Cognitive emotion regulation questionnaire- development of a short 18-item version (CERQ-short). Personality and Individual Differences. 41(6) 1045-1053. Garnefski N et al (2001). Negative life events, cognitive emotion regulation and emotional problems. Personality and Individual Differences.30(8) 1311-1327. Gross JJ (1998). The emerging field of emotion regulation: an integrative review. Review of General Psychology. 2(3) 271-299. Gross JJ (1999). Emotion regulation: Past, present, future. Cognition and Emotion. 13(5) 551-573. Gross JJ (2001). Emotion regulation in adulthood: Timing is everything. Current Directions in Psychological Science. 10(6) 214-219. Lang P (1994). The varieties of emotional experience: A meditation on James-Lange theory. Psychological Review. 101(2) 211-221. Lazarus RS (1993). Coping theory and research: Past, present, and future. Psychosomatic Medicine. 55(3) 234-247. Lazarus RS Folkman S (1984). Stress, appraisal and coping. New York: Springer. Lovibond SH Lovibond PF (2002). Manual for the depression anxiety stress scales (2nd ed.). Sydney: Psychology Foundation. Oatley K Johnson-Laird PN (1987). Towards a cognitive theory of emotions. Cognition and Emotion. 1(1) 29-50. Painuly N et al (2007). Antecedents, concomitants and consequences of anger attacks in depression. Psychiatry Research. 153(1) 39-45. Rothbart MK Ahadi SA (1994). Temperament and the development of personality. Journal of Abnormal نشریه دانشکده پرستاری و مامایی یهنخجتا. یهنخجتا. یمن یپهنمشسرجتا ن وا یگژوهسرا / 69 ب شش ر ظ Psychology. 103(1) 55-66. Tooby J Cosmides L (1990). The past explains the present: Emotional adaptations and the structure of ancestral environments. Ethology and Sociobiology. 11(4) 375-424. Troisi A D’Argenio A (2004). The relationship between anger and depression in a clinical sample of young men: the role of insecure attachement. Journal of Affective Disorders.79(1-3) 269-272. Veit CT Ware JE (1983). The structure of psychological distress and well-being in general population. Journal of Consulting and Clinical Psychology. 51(5) 730-742.